Pengaruh Pemberian Zat Pengatur Tumbuh Auksin Terhadap Pertumbuhan Anakan Karet Cabutan Alam (Hevea brasiliensis) - Nurhadiah Nurhadiah; Nining Sri Sukasih; Budi Rivan Kamulyan (Soilrens, 2021)
The development of rubber plantation in Sintang District continues to increase anually. Consequently, it is necessary to prepare a good rubber tiller. A Good rubber tiller can be obtained with the application of growth regulator when the tillers are ready to be planted. This study aimed to determine the effect of giving growth regulator Rootone-F on the growth of natural rubber saplings and to obtain a dose of Rootone-F growth regulator with the highest growth of natural rubber saplings.This study used a Randomized Block Design method, with one treatment (Rootone-F growth of regulator), consisted of 5 treatment levels: r0 = 0g Rootone-F per liter of water (control), r1 = 1g Rootone-F per liter of water, r2 = 2g Rootone-F per liter of water, r3 = 3g Rootone-F per liter of water, r4 = 4g Rootone-F per liter of water. Each treatment was repeated 4 times. Observations were made on these variables: plant height, leaves count, and stem diameter. The results showed that the Rootone-F growth regulator had the effect on the growth of natural rubber saplings. Highest growth was achieved at the dose of 2 g Rootone-F per liter of water, and based on the result of that dose there was an average increase in plant height (8.88 cm) and an average number of leaves (4.78 leaves).